2012
DOI: 10.2503/hrj.11.523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pinching and Lowering on Cucumber Yield and Yield Components

Abstract: The effects of pinching and lowering on cucumber yield and yield components were investigated. A short-term experiment was conducted on 3 cucumber (Cucumis sativus L.) cultivars grown hydroponically in a greenhouse from July to October 2011. Pinching plants were pinched at above 20 leaves on a main branch and at the 2nd leaf on the first lateral branches. Lowering plants were pinched at above 15-19 leaves on a main branch and not pinched on 4 lateral branches that were lowered with their growth. The fresh frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The growth characteristics and yield components have a large impact on crop yield and they can be organized into a hierarchical structure that explains the impacts of the various environmental factors on crop yield (Higashide and Heuvelink, 2009). In the past decade, studies on tomato and cucumber have identified several yield components and growth characteristics, and shown that fruit yield is positively correlated with dry matter production (Higashide and Heuvelink, 2009;Higashide et al, 2012aHigashide et al, , b, 2015Kaneko et al, 2015). Saito et al estimated tomato plant growth and dry matter production as a function of the environmental conditions (Saito et al, 2020b) and used those estimates to construct a model for yield prediction (Saito et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The growth characteristics and yield components have a large impact on crop yield and they can be organized into a hierarchical structure that explains the impacts of the various environmental factors on crop yield (Higashide and Heuvelink, 2009). In the past decade, studies on tomato and cucumber have identified several yield components and growth characteristics, and shown that fruit yield is positively correlated with dry matter production (Higashide and Heuvelink, 2009;Higashide et al, 2012aHigashide et al, , b, 2015Kaneko et al, 2015). Saito et al estimated tomato plant growth and dry matter production as a function of the environmental conditions (Saito et al, 2020b) and used those estimates to construct a model for yield prediction (Saito et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the initial increase in LAI is directly related to the yield in short-term cultivation, but the planting density results of Higashide et al (2012a) were 1.48 plants•m −2 and 0.99 plants•m −2 using the lowering and pinching methods, respectively, suggesting that the lowering method may not be suitable for short-term cultivation. In addition, Japanese cultivars have a low rate of female flowering on the main branches.…”
Section: Training Methodsmentioning
confidence: 96%
“…Considering this result from the viewpoint of the yield component, the increase in the number of fruits due to the increase in the number of nodes, and the increase in the amount of light reception due to the increase in the LAI caused by extending the side branches are the causes of the increase in the yield. Higashide et al (2012a) analyzed the effects of the lowering and pinching methods on dry matter production and yield in short-term cultivation from the yield components, and found that the pinching cultivation had a higher yield than that of lowering. They stated that the result was due to a higher proportion of fruit dry matter and total dry matter.…”
Section: Training Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR was assumed to be 43% of the global radiation for PO and 58% of the global radiation for TBF based on actual measurements. Light use efficiency (LUE) was calculated based on the method described by Itoh et al (2020) and Higashide et al (2012). We estimated the cumulative intercepted PAR by calculating daily LAI based on destructive analysis at transplanting, pinching, and the end of the cultivation and daily PAR based on the climate data recorded by the Ishigakijima local meteorological observatory (lat.…”
Section: Methodsmentioning
confidence: 99%